How institutional voids influence Brazilian foreign direct investment in Angola - Virches, Renato; Cahen, Fernanda Ribeiro (Internext, 2017)
How do institutional voids influence emerging market multinationals (EMNEs) foreign direct investment (FDI) in developing countries? In this article we respond to this question by examining Brazilian FDI in Angola as our analytical setting. We focus on the host country’s institutions and its institutional voids as essential factors that attract the FDI of EMNES to developing countries. The research indicates that Brazilian companies fill in much of these voids within the market intermediaries, often creating a point of competitive advantage, and also creating advantages in relation to FDI from other economies that invest in Angola. The scarce literature on FDI in Africa has been largely dedicated to the analysis of Chinese investment in the region. We aim to complement recent research on the influence of the host country’s institutions on the behavior of FDI in developing countries, explaining how some EMNEs are able to use the institutional voids of developing countries as market opportunities. Our findings should provide also implications for EMNEs managers from other emerging markets by providing a better understanding of how Brazilian multinationals expand their business in less developed countries, handle institutional voids and manage relationships with local and foreign institutions in the host country.